THE MEDIATING ROLE OF ONLINE PAYMENT IN THE RELATIONSHIP BETWEEN TIKTOK PRODUCT REVIEWS AND PURCHASE DECISIONS ON E-COMMERCE PLATFORMS - Duhita, Amanda Ridha Pradya (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
This study aims to examine the effect of product reviews on TikTok on consumer purchase decisions on the Tokopedia e-commerce platform, with online payment as a mediating variable. A quantitative approach was used by distributing a structured questionnaire to 100 purposively selected respondents in Surabaya who actively use TikTok and Tokopedia. Data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results show that product reviews have a positive influence on purchase decisions, both directly and through online payment. Online payment serves as a key factor that links consumer interest with actual purchasing behavior. The credibility of reviews and the ease of digital payment systems significantly strengthen purchasing decisions. These findings imply that e-commerce businesses and MSMEs should integrate social media content strategies with secure and convenient payment systems to increase conversions and enhance consumer experience.